Współdziałanie Sprężysto-Plastycznych Fal Naprężenia z Nieściśliwą Płaską Przegrodą Spoczywającą na Półprzestrzeni Sprężystej - Papliński, A.; Włodarczyk, E. (Engineering Transactions, 1972)
The paper presents a solution of the problem of interaction between an elastic-plastic unloading wave and an incompressible massive plate resting on a linearly elastic half-space and covered by a layer of soil of thickness h. The soil layer is approximated by a plastic medium with linear loading and rigid unloading branches (Fig. 1). Closed form solutions are analytically derived for the pressure acting over and under the plate. Extensive numerical analysis of the time-dependent reactions mentioned above is given. Approximate formulae suitable for practical engineering purposes are proposed.